Pengaruh Kecerdasan Emosional Dan Motivasi Belajar Terhadap Prestasi Belajar Siswa Sd Muhammadiyah 10 Tipes Surakarta Tahun 2015/2016 - Estu Ramadha, Yusadewa; , Muhroji, S.E, M.Si, M.Pd (2016)
This study aims to determine: (1) the effect of emotional intelligence on student achievement, (2) the effect of learning motivation on student achievement, (3) the influence of emotional intelligence and learning motivation on student achievement. This research is a quantitative research design ex posfacto. This study population is the class (IV, V, VI) 10 Tipes SD Muhammadiyah Surakarta. Mechanical sampling using stratified proportional random sampling. The technique of collecting data using questionnaires and documentation. Data were analyzed using multiple regression. Based on the results obtained by calculating the regression equation: Y = 41.345 + 0.247 + 0.197. Emotional intelligence t test results obtained t 2.550> 2.018 and motivation to learn obtained t 2.692> 2.018. While the test results obtained Fhitung 19.595 F> 3.23. Based on the analysis we can conclude that: 1) there is an influence of emotional intelligence on student achievement 10 Tipes SD Muhammadiyah Surakarta in 2015/2016. 2) there is influence learning motivation on student achievement 10 Tipes SD Muhammadiyah Surakarta in 2015/2016. 3) there is the influence of emotional intelligence and learning motivation on student achievement 10 Tipes SD Muhammadiyah Surakarta in 2015/2016. Emotional intelligence variables contribute effectively amounted to 23.6% and variable learning motivation by 25.3%. So that the total effective contribution given the two variables is 48.9%, while 51.1% is influenced by other variables not examined.